2004
DOI: 10.1111/j.1875-595x.2004.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in South Africa

Abstract: This study describes the oral health status of the inhabitants of, and reflects on possible trends in oral diseases in South Africa. During the past 20 years, three national oral health surveys were conducted in South Africa, the most recent, a national Children's Oral Health Survey, was conducted between 1999 and 2002. The results of this study show that 39.7% of the 6-year-old children were caries free, which is below the goal of 50% set by the Department of Health (DoH) for the year 2000. The DMFT of 1.1 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 3 publications
5
78
0
4
Order By: Relevance
“…While the exact extent of caries among this cohort was not noted, by the time children were referred for extractions, they presented with at least two carious teeth. Caries is prevalent among South African children and when the previous National Oral Health Survey was performed approximately 15 years ago caries among 6-year old South African children was 60.3% [34]. A survey conducted in 2006 among children from a nearby community to where the current study was performed, found the prevalence of early childhood caries among 4 and 5 year old children to be 55.8% and 53.4% respectively [35].…”
Section: Discussionmentioning
confidence: 99%
“…While the exact extent of caries among this cohort was not noted, by the time children were referred for extractions, they presented with at least two carious teeth. Caries is prevalent among South African children and when the previous National Oral Health Survey was performed approximately 15 years ago caries among 6-year old South African children was 60.3% [34]. A survey conducted in 2006 among children from a nearby community to where the current study was performed, found the prevalence of early childhood caries among 4 and 5 year old children to be 55.8% and 53.4% respectively [35].…”
Section: Discussionmentioning
confidence: 99%
“…(13) Translations are usually required for the informed consent forms and patient information brochures, however English is acceptable for the clinical protocols, CRFs and Investigators Brochures.…”
Section: Language Barriermentioning
confidence: 99%
“…One in three men and 50% of all women are overweight. (13) Increasing urbanisation and resultant unhealthy lifestyles, lead to the appearance of various chronic diseases of lifestyle risk factors such as hyperlipidaemia, diabetes, atherosclerosis, obesity, hypertension and an increasing tobacco addiction.…”
mentioning
confidence: 99%
“…The seeds and kernels especially add essential nutrients to the diet, and are available when other foods are scarce [1]. The main staple foods in Mozambique are cassava, maize, beans, sorghum and rice.…”
Section: Introductionmentioning
confidence: 99%